Therapeutic High‐Frequency Repetitive Transcranial Magnetic Stimulation Concurrently Improves Mood and Anxiety in Patients Using Benzodiazepines. Issue 3 (1st August 2019) - Caulfield, Kevin A.; Stern, Adam P.
Abstract : Objectives/Hypothesis: In this study, we tested the use of repetitive transcranial magnetic stimulation (rTMS) to reduce depression and anxiety in patients using or not using benzodiazepines. We hypothesized that rTMS would concurrently reduce symptoms in both depression and anxiety and that these reductions would correlate with patients using benzodiazepines. Materials and Methods: This retrospective study screened for patients treated in a TMS clinic within a five‐year period. Each patient had received high‐frequency (10 or 20 Hz) rTMS over the left dorsolateral prefrontal cortex and completed pre‐ and posttreatment Beck Depression Inventory and Visual Analog Scale‐Anxiety ratings. Fifty‐eight patients (37 women) met these criteria and 37 (63.8%) took benzodiazepines. We used two mixed analysis of variance analyses to separately evaluate the effects of rTMS on depression and anxiety. We additionally directly evaluated the relationship between reductions in depression and anxiety by computing three linear correlations (all patients, benzodiazepine users, nonbenzodiazepine users). Results: rTMS was an effective treatment of depression for all patients ( p < 0.001). rTMS also reduced anxiety scores from pre‐ to posttreatment ( p = 0.002). Furthermore, reductions in depression and anxiety were correlated ( p = 0.002). These changes in depression and anxiety only correlated with benzodiazepine users ( p < 0.001) and not nonbenzodiazepine users ( p = 0.608). Conclusions: rTMS concurrently improved both depression and anxiety, and changes in these measures correlated with patients using benzodiazepines. With further investigation, rTMS may be a helpful treatment for both anxiety and depression simultaneously.